2019
DOI: 10.4244/eij-d-18-01107
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cardiac computed tomography angiography and transoesophageal echocardiography for device surveillance after left atrial appendage closure

Abstract: Aims: Device surveillance after left atrial appendage (LAA) closure (LAAC) is important to assess device positioning, peri-device leak (PDL) and device-related thrombus (DRT). There are limited data on the role of cardiac CT angiography (CCTA) after LAAC. We therefore sought to compare CCTA to transoesophageal echocardiography (TEE) in patients who successfully underwent LAAC.Methods and results: We report our consecutive series of non-valvular atrial fibrillation patients who underwent LAAC and had CCTA and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
72
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 21 publications
7
72
0
1
Order By: Relevance
“…Moreover, sensitivity for assessing leak has been reported to be lower with TEE, especially the 2-D TEE, than other imaging methods. 5,14 In the current series, the same limitation of 2-D TEE was observed; inconclusive TEE in 44 patients with "NW" appearance were confirmed for the presence of leak by the 3-D TEE.…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, sensitivity for assessing leak has been reported to be lower with TEE, especially the 2-D TEE, than other imaging methods. 5,14 In the current series, the same limitation of 2-D TEE was observed; inconclusive TEE in 44 patients with "NW" appearance were confirmed for the presence of leak by the 3-D TEE.…”
Section: Discussionsupporting
confidence: 75%
“…(Table 3, Figure 3). In the three studies that reported the average gap size on both CCTA and TEE (12,19,20), the average gap size between the modalities was not significantly different. Four studies (11,15,18,20,21) evaluated adequate LAA device closure on CCTA by assessing both the peridevice gap and contrast enhancement in the LAA distal to the device.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 82%
“…In the three studies that reported the average gap size on both CCTA and TEE (12,19,20), the average gap size between the modalities was not significantly different. Four studies (11,15,18,20,21) evaluated adequate LAA device closure on CCTA by assessing both the peridevice gap and contrast enhancement in the LAA distal to the device. The prevalence of incomplete LAA closure in these studies was 60%, 98%, and 51%, amongst which 38%, 28%,43% of patients respectively had peridevice gap (27,30,32).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 82%
See 2 more Smart Citations